Misinterpretation of patience: an analytical study of nerimo concept within Indonesian Muslim society - Adang Kuswaya; Sukron Ma'mun (Indonesian Journal of Islam and Muslim Societies, 2020)
This research aims to deeply explore the nerimo concept in Javanese Muslim society. Nerimo as the philosophy of Javanese culture is often associated with the concept of patience in Islamic doctrine. This research shows that there are a misconception understanding and practice among the Javanese Muslims regarding the concept of nerimo and patience. They tend to express nerimo and patience as a practice of passivity, static, and blind submission to all problems of life. This causes the values contained those concepts to be reduced and lose the spirit of liberation for the life of mankind. By employing a liberation hermeneutic approach and sociological analysis, this research concludes that the nerimo concept in Javanese Muslim could be reconstructed into a Javanese idea that implies human endurance in every period of life. The concepts of nerimo and patience alternately are a form of psychological, spiritual, and intellectual awareness that every life has a periodic motion where every person will surely experience life fluctuations. Then the principle of patience and nerimo become a catalyst for the position of life to turn it back into motion. Patience and nerimo, therefore, are not placed as results but are situated as the power of a continuity life process which can drive people surpassing one stage of their lives.Penelitian ini bertujuan untuk mengeksplorasi konsep nerimo dalam masyarakat Muslim Jawa. Nerimo sebagai filosofi budaya Jawa sering dikaitkan dengan konsep kesabaran dalam doktrin Islam. Penelitian ini menunjukkan bahwa ada pemahaman dan praktik miskonsepsi di kalangan Muslim Jawa tentang konsep nerimo dan kesabaran. Mereka cenderung mengekspresikan nerimo dan kesabaran sebagai praktik kepasifan, statis, dan kepatuhan buta terhadap semua masalah kehidupan. Ini menyebabkan nilai-nilai yang terkandung dalam konsep-konsep tersebut menjadi berkurang dan kehilangan semangat pembebasan bagi kehidupan umat manusia. Dengan menggunakan pendekatan hermeneutika pembebasan dan analisis sosiologis, penelitian ini menyimpulkan bahwa konsep nerimo dalam Muslim Jawa sebenarnya dapat direkonstruksi menjadi gagasan Jawa yang menyiratkan ketahanan manusia dalam setiap periode kehidupan. Konsep nerimo dan kesabaran secara bergantian adalah bentuk kesadaran psikologis, spiritual, dan intelektual bahwa setiap kehidupan memiliki gerakan periodik di mana setiap orang pasti akan mengalami fluktuasi kehidupan. Maka prinsip kesabaran dan nerimo menjadi katalisator bagi posisi hidup untuk mengubahnya kembali menjadi gerak. Kesabaran dan nerimo, oleh karena itu, tidak ditempatkan sebagai hasil tetapi ditempatkan sebagai kekuatan dari proses kehidupan berkelanjutan yang mampu mendorong orang melampaui satu tahap kehidupan mereka.